Characterization of crack growth resistance under thermal shock on silicon nitride with various microstructure - Takenobu SAKAI (The Japan Society of Mechanical Engineers, 2014)
The crack growth resistance under thermal shock loading on silicon nitride was characterized using Disc-on-Rod test which was developed by the authors. The microdamage during thermal shock fracture was monitored by acoustic emission (AE) technique. Specimens were composed of β-Si3N4 with an acicular structure. Cylinders of silicon nitride with various microstructures were sintered at different temperatures. A pre-crack was introduced using Knoop indentation. In the Disc-on-Rod test, the specimens were uniformly heated to 850 ºC, and only the center of circular specimen was quenched by contacting with a copper rod. Within a fraction of a second after contacting, crack propagated in an unstable manner, at the same time, a high amplitude AE signal was detected. Subsequently, stable crack propagation was observed, and several low amplitude AE signals were generated corresponding to crack propagation. The specimen sintered at higher temperature showed lower crack growth resistance. From the results of microstructure observation and the fracture mechanical consideration, it is suggested that larger grains with > 1.5 μm in minor axes contribute to the toughening of materials. Consequently, the results of this study provide fundamental insights for the development of ceramic materials with high resistance to thermal shock fracture.